2002
DOI: 10.3748/wjg.v8.i6.1144
|View full text |Cite
|
Sign up to set email alerts
|

Cyclospore cayetanensisin Anhui, China

Abstract: Cyclospore cayetanensis infection is present in Anhui, China and it was confirmed to be a new pathogen associated with children diarrhea, adults obstinate diarrhea and diarrhea in immunocompromised individuals. Among all the infected individuals, adult obstinate diarrhea patients and immunocompromised individuals are common. Feces examination of oocysts and serological examination of the specific antibody will be of much help in the diagnosis of Cyclospore cayetanensis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 50 publications
2
17
2
1
Order By: Relevance
“…Attempts toinfect several animals with C. cayetanensis have been unsuccessful, suggesting host specificity (Eberhard et al, 2000). Although C. cayetanensis was reported to be propagated in albino mice (Sadaka et al, 2001) and guinea pigs (Wang et al, 2002) the findings could not be confirmed (Ortega et al, 2010). The parasite has been detected in shellfish (Negm, 2003;Aksoy et al, 2014).…”
Section: Reservoirs: the Role Of Animals In Transmissioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Attempts toinfect several animals with C. cayetanensis have been unsuccessful, suggesting host specificity (Eberhard et al, 2000). Although C. cayetanensis was reported to be propagated in albino mice (Sadaka et al, 2001) and guinea pigs (Wang et al, 2002) the findings could not be confirmed (Ortega et al, 2010). The parasite has been detected in shellfish (Negm, 2003;Aksoy et al, 2014).…”
Section: Reservoirs: the Role Of Animals In Transmissioncontrasting
confidence: 41%
“…The findings indicated an inverse relationship between socioeconomic status and infection and showed that cyclosporiasis, as well as other communicable infections, affects families living in substandard housing developments. In Haiti and China, higher rates of infection have been noted in areas, where deficient sanitary facilities and personal hygiene and soil frequently contaminated with feces were present (Lopez et al, 2003;Wang et al, 2002;Zhou et al, 2011). with low socioeconomic status rather than age alone.…”
Section: Waterborne Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assays used oocysts produced in guinea pigs. This animal model and serological testing need to be reproduced and validated by other scientists (191). A Western blot assay has been developed and can identify acute-from convalescent-phase cyclosporiasis (Y. R. Ortega, unpublished data).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Nonetheless, it cannot yet be ruled out that animals may play a role in the dissemination of Cyclospora by contaminating water and food products. Two reports indicate that Cyclospora can be propagated in guinea pigs (191) and albino mice (162). These studies could not be reproduced, and further analyses are needed to determine the susceptibility of these animals to infection by Cyclospora and their suitability as hosts or reservoirs of C. cayetanensis.…”
Section: Life Cyclementioning
confidence: 99%